The Abstract Concept of Multicultural Society in the Architecture of the South of Thailand: Chinese art style - Tulee, Somporn (RMUTK Journal of Liberal Arts, 2023)
This research aimed to employ abstract thinking to analyze artistic elements, Buddhist content, and a form of expression that combines the diversity of multiculture in the Rattanakosin period (Rama 1-Rama IX) of 19 temples and to preserve and promote cultural tourism in the Buddhist art of the South. The results revealed that abstract concept of multicultural Chinese art form in the architecture of the South consisted of concrete creative elements including Buddhism and beliefs, traditions, ways of life in Chinese art and local beliefs in the south that were shown in the architecture related to the society of the South anchored by Buddhist ways of life and beliefs. This concept was linked through concrete expression in different shapes mingled in the work, resulting in aesthetics, ways of thinking, and tastes that were expressed straightforwardly and simply. Diversity was also found in unity. The combination of Chinese art forms seemed to embrace unity in architecture. This could produce a set of knowledge that involved historical value and wisdom reflecting beliefs, faith, traditions, arts and culture, ways of life, and communities of the South.